One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile

One-step method for the synthesis of aryl olefins from aryl aldehydes and aliphatic aldehydes - Borate, Hanumant B.; Gaikwad, Supriya H.; Kudale, Ananada S.; Chavan, Subhash P.; Pharande, Shrikant G.; Wagh, Vitthal D.; Sawant, Vikram S. (Tetrahedron Letters, 2013)
A conceptually new one-step reaction affording unexpected aryl olefinic product from aromatic aldehyde, aliphatic aldehyde and malononitrile in the presence of acetic acid-ammonium acetate under mild reaction conditions without using any metal catalyst is reported. This novel reaction was used to prepare a number of substituted aryl olefins including new molecules. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aliphatic aldehyde; Aromatic aldehyde; Aryl olefin; Dicyanoaniline; Malononitrile